1 Answer | Add Yours
To answer this, you need to remember the formula for area of a rectangle:
`A = l*w`
Here, `A` is the area, `l` is the length, and `w` is the width.
We are given the information for the area and the length, so we can substitute the given expressions into our equation:` `
`2x^2-x-1 = (2x+1)w`
To solve this equation for `w`, we must divide both sides by `2x+1`:
`(2x^2-x-1)/(2x+1) = w`
Now, we need to evaluate the expression on the left. The easiest way to do this is to factor the expression in the numerator, giving us:
`((2x+1)(x-1))/(2x+1) = w`
We can now cancel out `2x+1` from the top and bottom to yield our answer:
`x-1 = w`
Another way to do this is through polynomial long division, which is not easily displayed in the formats available to us:
`2x+1` / `2x^2-x-1`
Your first part of the quotient will be "`x`":
`(2x^2-x-1)-(2x+1)(x) = 2x^2-x-1 - 2x^2 - x = -2x-1`
The second part of the quotient will be "-1":
`-2x-1 - (2x+1)(-1) = -2x-1+2x+1 = 0`
We have a zero result after the division, indicating our quotient is `x-1`.
Either way, we have the same result: width = `x-1` .
We’ve answered 333,747 questions. We can answer yours, too.Ask a question